Regulation of Syk activity by antiviral adaptor MAVS in FcεRI signaling pathway - Yuko Kawakami; Miho Kimura; Christella Widjaja; Kazumi Kasakura; Tomoaki Ando; Yu Kawakami; Joshua J. Obar; Toshiaki Kawakami (Frontiers in Allergy, 2023)
BackgroundMast cells are the major effector cell type for IgE-mediated allergic reactions. Recent studies revealed a role for mast cells in orchestrating the host response to viral infections.ObjectiveWe studied the relationship between FcεRI (high-affinity IgE receptor) and RIG-I-like receptor (RLR)-mediated antiviral signaling pathways.MethodsMast cells (BMMCs) were cultured from bone marrow cells from mice deficient in MAVS or other RLR signaling molecules. MAVS expression was restored by retroviral transduction of MAVS-deficient BMMCs. These cells were stimulated with IgE and antigen and their activation (degranulation and cytokine production/secretion) was quantified. FcεRI-mediated signaling events such as protein phosphorylation and Ca2+ flux were analyzed by western blotting and enzyme assays. WT and mutant mice as well as mast cell-deficient KitW−sh/W−sh mice engrafted with BMMCs were subjected to passive cutaneous anaphylaxis.ResultsUnexpectedly, we found that mast cells devoid of the adaptor molecule MAVS exhibit dramatically increased cytokine production upon FcεRI stimulation, despite near-normal degranulation. Consistent with these observations, MAVS inhibited tyrosine phosphorylation, thus catalytic activity of Syk kinase, the key signaling molecule for FcεRI-mediated mast cell activation. By contrast, mast cells deficient in RIG-I, MDA5 or IRF3, which are antiviral receptor and signaling molecules upstream or downstream of MAVS, exhibited reduced or normal mast cell activation. MAVS-deficient mice showed enhanced late-phase responses in passive cutaneous anaphylaxis.ConclusionThis study demonstrates that the adaptor MAVS in the RLR innate immune pathway uniquely intersects with the adaptive immune FcεRI signaling pathway.